Correlates of Infrequent Plain Water Intake Among US High School Students: National Youth Risk Behavior Survey, 2017. Issue 5 (June 2020) - Park, Sohyun; Onufrak, Stephen; Cradock, Angie; Patel, Anisha; Hecht, Christina; Merlo, Caitlin; Blanck, Heidi M.
Purpose: To examine factors associated with frequency of plain water (ie, tap, bottled, and unflavored sparkling water) intake among US high school students. Design: Quantitative, cross-sectional study. Setting: The 2017 national Youth Risk Behavior Survey data. Subjects: US high school students with plain water intake data (N = 10 698). Measures: The outcome was plain water intake. Exposure variables were demographics, academic grades, and behavioral characteristics. Analysis: We used logistic regression to estimate adjusted odds ratios (aOR) and 95% confidence intervals (CIs) for factors associated with infrequent plain water intake (<3 vs ≥3 times/day). Results: Overall, 48.7% of high school students reported drinking plain water <3 times/day. Factors associated with infrequent plain water intake were younger age (≤15 years; aOR = 1.20, CI = 1.05-1.37); earning mostly D/F grades (aOR = 1.37, CI = 1.07-1.77); consuming regular soda 1 to 6 times/week (aOR = 1.92, CI = 1.67-2.20) or ≥1 time/day (aOR = 3.23, CI = 2.65-3.94), sports drinks 1 to 6 times/week (aOR = 1.30, CI = 1.14-1.49), milk <2 glasses/day (aOR = 1.51, CI = 1.31-1.73), fruits <2 times/day (aOR = 1.92, CI = 1.66-2.22), and vegetables <3 times/day (aOR = 2.42, CI = 2.04-2.89); and being physically active ≥60 minutes/day on <5 days/week (aOR = 1.83, CI = 1.60-2.08). Students with obesity were less likely to have infrequent water intake (aOR = 0.63, CI = 0.53-0.74). Conclusions: Infrequent plain water intake was associated with younger age, poor academic grades, poor dietary behaviors, and physical inactivity. These findings can inform intervention efforts to increase water intake to promote healthy lifestyles among adolescents.